2015
DOI: 10.1038/ncomms7812
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the oxidation of soot to its redox cycling abilities

Abstract: Although it is known that soot particles are emitted in large quantities to the atmosphere, our understanding of their environmental effects is limited by our knowledge of how their composition is subsequently altered through atmospheric processing. Here we present an on-line mass spectrometric study of the changing chemical composition of hydrocarbon soot particles as they are oxidized by gas-phase ozone, and we show that the surface-mediated loss rates of adsorbed polycyclic aromatic hydrocarbons in soot are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
100
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(110 citation statements)
references
References 45 publications
7
100
1
2
Order By: Relevance
“…Generally, DTT t of NSOA filter under O 3 exposure was higher than that of N 2 exposure. The study of Antiñolo et al (2015) also showed an increased redox activity of soot accompanied by an increased amount of oxygenated derivatives (quinone) under heterogeneous oxidation. However, the enhanced oxidative capacity from heterogeneous ozonolysis appeared to decrease with longer exposure to O 3 (Fig.…”
Section: Op From Heterogeneous Oxidationmentioning
confidence: 99%
See 4 more Smart Citations
“…Generally, DTT t of NSOA filter under O 3 exposure was higher than that of N 2 exposure. The study of Antiñolo et al (2015) also showed an increased redox activity of soot accompanied by an increased amount of oxygenated derivatives (quinone) under heterogeneous oxidation. However, the enhanced oxidative capacity from heterogeneous ozonolysis appeared to decrease with longer exposure to O 3 (Fig.…”
Section: Op From Heterogeneous Oxidationmentioning
confidence: 99%
“…Specific molecular characteristics of these high MW OP contributors are currently unknown, and understanding them will be the subject of future research. It is very likely that the oligomers also contain redox-active quinone functional groups, such as those formed on the surface of oxidized soot (Antiñolo et al, 2015), and are therefore important for OP.…”
Section: Op Of Oligomers In Nsoamentioning
confidence: 99%
See 3 more Smart Citations